Long-COVID in patients with a history of mild or asymptomatic SARS-CoV-2 infection: a Nationwide Cohort Study. (3rd July 2022) - Adler, Limor; Gazit, Sivan; Pinto, Yuval; Perez, Galit; Mizrahi Reuveni, Miri; Yehoshua, Ilan; Hoffman, Robert; Azuri, Joseph; Patalon, Tal
Abstract: Objective: Evaluating the prevalence of long-COVID symptoms in patients with a history of mild or asymptomatic infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and the factors associated with developing long-COVID. Design: A nationwide cohort study. Using a centralized database, we have identified patients with and without a history of SARS-CoV-2 infection 1–6 months before data collection. Patients were asked to fill out an online questionnaire through text messages. Setting: Israeli general practice. Subjects: 2755 persons participated in the study in September 2021 (a response rate of 7.5%): 819 with and, 936 without a history of SARS-CoV-2 infection. Main outcome measures: We asked patients to provide details about their demographic status, medical history, COVID-related variables and the presence of long-COVID symptoms. Results: Most prevalent long-COVID symptoms were decreased smell sensation (35.1% vs. 4.3%, p  < 0.001), decreased taste sensation (25.2% vs. 3.2%, p  < 0.001), memory disturbances (36.9% vs. 14.4%, p  < 0.001), dyspnea (24.2% vs. 10.7%, p  < 0.001) and arthralgia (33% vs. 16.3%, p  < 0.001). Risk factors associated with long-COVID included female gender, symptomatic COVID-19, overweight or obesity and the presence of dyslipidemia. About 34.6% of participants reported not returning to their baseline health condition after the acute illness. Conclusion: Long-COVID is frequently seen following a mild symptomatic COVID-19 infection and, to a lesser extent, following an asymptomatic SARS-CoV-2 infection. Primary care physicians should be aware of these symptoms and consider this option in their differential diagnosis. Health policymakers should expect a significant impact of this syndrome on public health. Key Points: Long-COVID has emerged as a significant health problem with a serious impact on normal daily function Long-COVID symptoms were evident in patients with mild symptomatic disease and in asymptomatic patients to a lesser extent. Risk factors for having Long-COVID symptoms include female gender, symptomatic disease, increased BMI, and the presence of dyslipidemia. Fatigue, dyspnea, weakness, decreased libido, weight changes, memory, and sleep disturbances were associated with not returning to the baseline health state.